INFLUENCE OF BIOCHAR AND INORGANIC FERTILIZER ON UPLAND RICE-COWPEA INTERCROP COMPETITIVE INDICES (The Proceedings of The International Conference on Climate Change, 2022)
A trial was conducted to evaluate the competitive indices of upland rice-cowpea intercrop. Sole cropping of the two crops was also done. The experiment was a randomized complete block with 4 replications. The treatment included a control (no input), fertilizer, rice and cowpea intercrop either applied alone or in combination with three different sources of biochar (poultry manure, corn cobs and groundnut shell). At the same time 5 t ha-1 of biochar level each were incorporated into the soil. Inorganic fertilizer was applied at the rate of 90, 60, 60, and 45 kg ha-1 NPK, as straight fertilizer, and then top-dressed with nitrogen levels in the form of urea at 30 kg ha-1 N eight (8) weeks after transplanting. The crops were arranged in a 3:1 rice-cowpea ratio. In this study, intercropping system gave higher land equivalent ratio (LER). Biochar of poultry manure+45N30P30K exhibited higher rice aggressivity (2.43), relative crowding coefficient (1.74) and competitive ratio (4.11). Rice performed better in terms of competitive ratio when grown in combination with cowpea. In terms of nutrient use efficiency nitrogen was high with intercrops, but was very low in sole crop. Intercropping of rice with cowpea gave higher economic advantage (9544.5), income equivalent ratio (403.1), production and cost benefit ratio for biochar poultry manure+45N30P30K (2.68) than 90N60P60K (2.52) respectively. For economic crop yield in upland rice-based ecosystems, small-holder farmers, therefore, should intercrop rice and cowpea and apply biochar +45N30P30K and nitrogen (30 kg N ha-1).
Keywords: Land equivalent ratio; intercropping; biochar; inorganic fertilizer